2017
DOI: 10.5459/bnzsee.50.3.365-393
|View full text |Cite
|
Sign up to set email alerts
|

Reconnissance report on geotechnical and geological aspects of the 14-16 April 2016 Kumamoto earthquakes, Japan

Abstract: On 16 April 2016, a moment magnitude (Mw) 7.0 earthquake struck the Island of Kyushu, Japan. Two major foreshocks (Mw 6.2 and Mw 6.0) contributed to devastation in Kumamoto City, Mashiki Town and in the mountainous areas of the Mount Aso volcanic caldera. This report summarises geotechnical and geological aspects of the earthquakes that were observed during a field investigation conducted by the NZSEE Team in collaboration with Japanese engineers and researchers. Many houses and other buildings, roads, riverba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Subsequent earthquake reconnaissance visits to learn from earthquakes outside of New Zealand organised and led by the New Zealand Society for Earthquake Engineering and dissemination of the findings through lecture tours around New Zealand, such as after the 1994 Kobe earthquake in Japan [3], the 2008 Wenchuan earthquake [4] and the 2016 Kumamoto earthquake [5] provided additional information on the performance of lifeline infrastructure and impetus to lifelines studies and engineering. Lifelines groups were created around New Zealand following the examples set by Wellington and Canterbury, followed by the National Lifelines Council, which have co-ordinated the assessment and enhancement of lifeline infrastructure around New Zealand.…”
Section: Contextmentioning
confidence: 99%
“…Subsequent earthquake reconnaissance visits to learn from earthquakes outside of New Zealand organised and led by the New Zealand Society for Earthquake Engineering and dissemination of the findings through lecture tours around New Zealand, such as after the 1994 Kobe earthquake in Japan [3], the 2008 Wenchuan earthquake [4] and the 2016 Kumamoto earthquake [5] provided additional information on the performance of lifeline infrastructure and impetus to lifelines studies and engineering. Lifelines groups were created around New Zealand following the examples set by Wellington and Canterbury, followed by the National Lifelines Council, which have co-ordinated the assessment and enhancement of lifeline infrastructure around New Zealand.…”
Section: Contextmentioning
confidence: 99%
“…It is interesting to contrast the outcomes of the 2010-11 Christchurch earthquakes with the 2016 Kumamoto earthquakes. The NZSEE structural [12] and geotechnical [13] reconnaissance teams concluded that although the shaking resulting from the Kumamoto earthquakes was similar to Christchurch, the damage outcomes for modern buildings were typically better in Japan and the disruption to the city was considerably less. There are many contributing factors, but some notable points are:…”
Section: A Brief Comparison With Japanmentioning
confidence: 99%
“…On 16 April 2016, a relatively gentle slope (12 • -15 • ) located within the Mt. Aso Volcanic Caldera, in the Prefecture of Kumamoto (Kyushu Island, Japan), failed catastrophically due to severe ground shaking induced by the moment magnitude M w 7.0 2016 Kumamoto Earthquake [1][2][3][4]. The resulting flow-type slide, which involved weathered volcanic soil deposits on a gentle slope, destroyed seven houses (causing five fatalities), damaged critical lifelines and local roads in the small residential Takanodai Housing Complex (Minamiaso Village), and threatened the neighboring Tokyu Country Town community.…”
Section: Introductionmentioning
confidence: 99%
“…Between April and October 2016, as a part of the Japan Society of Civil Engineers (JSCE) "Kumamoto Earthquake Damage Reconnaissance Mission", the New Zealand Society for Earthquake Engineering "Learn from Earthquake-Kumamoto Mission", and the "J-Rapid Japan-NZ Collaborative Kumamoto Project", a research team involving the first two authors carried out post-earthquake damage reconnaissance surveys and geotechnical field investigations in the area of the Mt. Aso Caldera affected by the earthquake [3,4]. The research team carried out a comprehensive investigation program consisting of geological and geotechnical characterization of the Takanodai landslide site involving sampling of volcanic soils for subsequent geotechnical laboratory testing and static and time-history seismic slope stability analyses.…”
Section: Introductionmentioning
confidence: 99%